2022
DOI: 10.2478/aoas-2022-0029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the growth of genetically improved tilapia Oreochromis niloticus reared at different temperatures

Abstract: This study aimed to evaluate the growth and performance of genetically improved tilapia reared at different temperatures. Four hundred and eighty fingerlings of Genomar Supreme Tilapia, GST (8.39 ± 0.60 g) were equally separated into three indoor water recirculation systems maintained at 22, 26 and 30 ºC. Each of four tanks contained 500 liters with 40 fish per tank in natural photoperiod. The fish were fed ad libitum with the same feed for each growth phase, weighing the total feed supplied. After 30 min of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Feed intake significantly increased with increasing culture temperature and CP levels, which is consistent with previous studies (Bendiksen et al, 2002;Fatma & Ahmed, 2020;Huang et al, 2016;Peres & Oliva-Teles, 1999;Santos et al, 2022;Van Ham et al, 2003) that demonstrated that increasing the culture temperature increased feed intake. Increase in feed intake with increasing culture temperature can be explained as increased temperature boosts the protease activities, as evident in our results, which speed up the digestion process that led to more feed consumption (Volkoff & Rønnestad, 2020).…”
Section: Digestive Enzyme Activitiessupporting
confidence: 92%
“…Feed intake significantly increased with increasing culture temperature and CP levels, which is consistent with previous studies (Bendiksen et al, 2002;Fatma & Ahmed, 2020;Huang et al, 2016;Peres & Oliva-Teles, 1999;Santos et al, 2022;Van Ham et al, 2003) that demonstrated that increasing the culture temperature increased feed intake. Increase in feed intake with increasing culture temperature can be explained as increased temperature boosts the protease activities, as evident in our results, which speed up the digestion process that led to more feed consumption (Volkoff & Rønnestad, 2020).…”
Section: Digestive Enzyme Activitiessupporting
confidence: 92%